The general principles of the Chinese contract law from the perspective of an (English) Common lawyer - Twigg-Flesner, Christian (Cambridge University Press, 2017)
This chapter will contrast the statement of general principles found in Arts.1-7 of the Chinese Contract Law (“CCL”) with the approach to general principles of contract law in the (English) common law. The particular purpose of this paper will be on how these two contract law regimes regard contractual freedom and the extent to which there are limitations to this. It will begin with a short summary account of the CCL’s general principles. The bulk of this paper will then set out the English common law’s approach to general principles, the notion of “freedom of contract”, and the extent to which restrictions to this notion are imposed by the common law. It must be stressed from the outset that this paper is concerned with English variant of the common law and how this contrasts with the CCL. There are, of course, different versions of the common law, and whilst these have common origins, significant variations have developed over time. Secondly, as will be explained, this paper is only concerned with the common law of contracts, and will not consider the way English law now regulates specific types of contracts, such as consumer contracts.